The Role of EMMPRIN in Perirenal Fat Invasion Clear Cell Renal Cell Carcinoma - Vira Yasmina Ramadhani1,2,3, Anny Setijo Rahaju4,5,6, Nila Kurniasari4,5,6 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Renal Cell Carcinoma (RCC) is a common malignancy of the kidney, and Clear Cell Renal Cell Carcinoma(CCRCC) is the most common type. Accurate prediction of prognosis is valuable for therapy and followup. EMMPRIN is a transmembrane protein of the immunoglobulin family and is associated with tumourproliferation, invasion and metastasis. This study aims to prove the role of EMMPRIN in perirenal fatinvasion CCRCC. This analytic observational study with a cross-sectional approach conducted in AnatomicalPathology Institute of Dr. Soetomo Hospital, Surabaya that used 44 samples of paraffin blocks from radicalnephrectomy preparations for CCRCC patients at the period of January 2013-December 2018, which weredivided based on perirenal fat invasion status. The analyzed was using Spearman test. EMMPRIN expressionis positively correlated with perirenal fat invasiveness (p = 0.019) in clear cell renal cell carcinoma.EMMPRIN expression is related with perirenal fat invasiveness, in clear cell renal cell carcinoma.